Pengetahuan dan Perilaku Pencegahan Infeksi Luka Jahitan Persalinan Grade 2 dengan Antibiotik - Laporan Kasus Ibu dengan Kehamilan Berisiko Tinggi - Lisa Herliyana; Anita Purnamayanti, S.Si., M.Farm-Klin.; Fransiscus Octavianus Hari Prasetyadi (Journal of Islamic Pharmacy, 2021)
Fetal breeching presentation is position of fetus with his bottom-first in the maternal’s uterus. It will increase risk of perinatal or neonatal mortality and morbidity, if breech presentation persisted at term. During labor, a woman could experienced perineal tears wound due to the impact of contraction pressure on intact perineum – especially for primiparous woman and heavier birth weight – as well as to episiotomy. The degree of perineal tears wound are classified as the first and second grade which are being considered as at low risk of infection and there is no indication of prophylactic antiobiotics; while the third and fourth degree perineal trauma are compulsory to be given antibiotics due to the higher risk of infection. This is cases of two multiparous women whose maternal status during antenatal care presented at Puskesmas – a pirmary healthcare facility in Indonesia – one patient with breech position at weeks 29- 34 and the other one was on chonic energy deficiency who were constantly in low blood pressure (BP) of 100/60 mmHg, MAP 73,3 mmHg, and poor nutritional state. The patients came from low social-economic and education. Healthcare team at Puskesmas provided childbirth education including perineal tears wound care, and pharmacist served medication literacy assistance due to lack of knowledge about their medication administration. This pharmacist’s assistance was delivered on hybrid system due to Covid-19 pandemic. The patient managed to deliver the baby on vaginal birth with second degree perineal tears and started on antibiotics, analgesics, vitamin A, and iron tablets.  One of the patient presented with fever, BP of 90/60 mmHg, and wound infection on day-3 postpartum; thus received another cure of antibotics and analgesic. The patients’ knowledge were improved, drug compliance were 100%, perineal tears wound care had been done properly, so that the wound completely dried and healed on day-42 postpartum.  Keywords: antibiotics, high risk, perineal wound, knowledge, behaviour.